2023
DOI: 10.1186/s12889-022-14677-6
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation and sociodemographic correlates of prescription psychotropic drug use among children and youth in Ontario, Canada: a population-based study

Abstract: Background Population-based research examining geographic variability in psychotropic medication dispensing to children and youth and the sociodemographic correlates of such variation is lacking. Variation in psychotropic use could reflect disparities in access to non-pharmacologic interventions and identify potentially concerning use patterns. Methods We conducted a population-based study of all Ontario residents aged 0 to 24 years who were dispen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…We are also unable to determine if certain demographic groups or regions are underrepresented in the data. This may be especially important for low-income children and youth, who our prior research demonstrated were more likely to receive antipsychotics than those from higher-income families ( 54 ). Furthermore, findings of disproportionate increases in antipsychotic use among specific sub-populations of children and youth could have ethical implications if related to differential access to non-pharmacologic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…We are also unable to determine if certain demographic groups or regions are underrepresented in the data. This may be especially important for low-income children and youth, who our prior research demonstrated were more likely to receive antipsychotics than those from higher-income families ( 54 ). Furthermore, findings of disproportionate increases in antipsychotic use among specific sub-populations of children and youth could have ethical implications if related to differential access to non-pharmacologic treatments.…”
Section: Discussionmentioning
confidence: 99%